USE OF THE BRAILLE BOX MEDIA TO INCREASE THE ABILITY OF READING BEGINNING IN BLIND CHILDREN IN SKh AL KHAIRIYAH CILEGON - Yayang Vaiza Usnawa; Tati Nurul Hayati; Reza Febri Abadi; Aniya Plb; Hardiyanti Kartika Putri (Jurusan Pendidikan Luar Biasa, FKIP Universitas Sultan Ageng Tirtayasa, 2019)
In its activities children with visual impairments experience obstacles in learning in accordance with their neutrality. Blind children who have difficulty reading braille, especially in remembering points on braille often students forget the position of the braille point they will read. Therefore there needs to be support in the learning process in the form of learning media. The use of braille boxes is used as a medium to improve the ability to read the beginning of blind children. This media braille box is not only used in educational learning but can be used as a game for blind children. This media braille box utilizes the senses of touching the blind child in using the media. Therefore, the use of this media braille box can be applied to increase reading interest and train the senses of touch on blind children.